2002
DOI: 10.1046/j.1528-1157.2002.11301.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging in the Study of the Lithium–Pilocarpine Model of Temporal Lobe Epilepsy in Adult Rats

Abstract: Summary:Purpose: In temporal lobe epilepsy, it remains to be clarified whether hippocampal sclerosis is the cause or the consequence of epilepsy. We studied the temporal evolution of the lesions in the lithium-pilocarpine model of epilepsy in the rat with magnetic resonance imaging (MRI) to determine the progressive morphologic changes occurring before the appearance of chronic epilepsy.Methods: MRI was performed on an MR scanner operating at 4.7 T. We followed the evolution of lesions using T 2 -and T 1 -weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
130
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 170 publications
(158 citation statements)
references
References 51 publications
26
130
0
2
Order By: Relevance
“…Consistent with chemically-induced SE models, SE induced by electrical stimulation of the rat amygdala resulted in increased T 2 values in the amygdala beginning 2 days after SE [21], and increased T2W signal intensity in the hippocampus 2 weeks after kindling had ceased [22]. Taken together, these findings suggest temporal complexities in T 2 signal changes occurring in post-SE TLE models, likely representing the evolving pathophysiological processes in epileptogenesis [16,17] that must be clarified and considered when translating the use of T 2 -based biomarkers to the clinical setting.…”
Section: Signal Changessupporting
confidence: 64%
See 2 more Smart Citations
“…Consistent with chemically-induced SE models, SE induced by electrical stimulation of the rat amygdala resulted in increased T 2 values in the amygdala beginning 2 days after SE [21], and increased T2W signal intensity in the hippocampus 2 weeks after kindling had ceased [22]. Taken together, these findings suggest temporal complexities in T 2 signal changes occurring in post-SE TLE models, likely representing the evolving pathophysiological processes in epileptogenesis [16,17] that must be clarified and considered when translating the use of T 2 -based biomarkers to the clinical setting.…”
Section: Signal Changessupporting
confidence: 64%
“…These acute changes typically return to baseline within 48-72 h [15,20], and have been reported to predict the development of epilepsy at 4 months after SE [15]. However, in contrast to these findings, other studies have reported a global decrease in T 2 values in the acute stages after SE [17], and evidence of T2W hyperintensity for up to 9 weeks after SE [16]. Consistent with chemically-induced SE models, SE induced by electrical stimulation of the rat amygdala resulted in increased T 2 values in the amygdala beginning 2 days after SE [21], and increased T2W signal intensity in the hippocampus 2 weeks after kindling had ceased [22].…”
Section: Signal Changesmentioning
confidence: 94%
See 1 more Smart Citation
“…This enzymatic downregulation does not seem to be the main underlying cause of the generation of spontaneous seizures in the Li-pilo model of TLE since glutamine synthesis appears normal in astrocytes. However, both cell bodies and astrocytic processes are hypertrophic in this model (Roch et al, 2002). If the larger volume occupied by this cell type is taken into account, a downregulation of GS may also take place in the present study.…”
Section: Tricarboxylic Acid Cycle Derived Metabolites In the Hippocammentioning
confidence: 52%
“…In Li-pilotreated rats, changes in astrocytes were mainly characterized by hypertrophy of cell bodies and processes near the lesions rather than an increase in astrocyte number (Roch et al, 2002). Furthermore, in the pilocarpine model, only half of the chronically epileptic rats had reactive astrocytes in thalamic, hippocampal, amygdalar, and neocortical areas (Garzillo and Mello, 2002).…”
Section: Tricarboxylic Acid Cycle Derived Metabolites In the Hippocammentioning
confidence: 97%